From waste to innovative value: The role of lean manufacturing techniques in accelerating the new industrial product lifecycle (A case study) - Eddine, Noureddine Ahmed Houssam; Mohamed, Chegrani; Aissa, Smail (The International tax journal, 2026)
This research investigates the critical impact of Lean Manufacturing (LM) techniques on the acceleration of the New Industrial Product Lifecycle (NPLC), transitioning from waste-focused paradigms to innovation-centric value models. Utilizing tools such as Value Stream Mapping (VSM), Just-in-Time (JIT), and Kaizen, the report analyzes how the systematic elimination of "Muda" (waste) liberates resources for Research and Development (R&D). Through a multi-regional analysis of global benchmarks (Toyota, Boeing, FedEx), Gulf Cooperation Council (GCC) leaders (SABIC, Saudi Aramco, Emirates Global Aluminium), and the Algerian industrial sector (ENIE, Condor, Nestlé Waters), the research demonstrates that organizations adopting "Lean Innovation" can reduce lead times by up to 50% and improve cycle efficiency by 35.5%. The findings confirm that while technical tools are essential, success in developing and transitioning economies depends on a synergy between organizational agility, cultural transformation, and proactive state-level strategic support.